Changing strategy and implementation of a new treatment protocol for cleft palate surgery in "Maria Sklodowska Curie" (MSC) Children's Hospital, Bucharest, Romania. Issue 6 (December 2014) - Spataru, Radu; Mark, Hans
Abstract In "Maria Sklodowska Curie" (MSC) Children's Hospital, Bucharest, Romania, cleft palate repair has been performed according to von Langenbeck since 1984. The speech was good in most patients but wide clefts had a high percentage of fistulas, abnormal speech due to short length and limited mobility of the soft palate. In 2009, the protocol was changed to Gothenburg Delayed Hard Palate Closure, (DHPC) technique. The present evaluation was performed to study the implementation of this technique. One hundred and sixty-eight patients with cleft palate were admitted, 89 isolated cleft palate (ICP), 53 unilateral (UCLP) and 26 bilateral (BCLP). In these, 228 surgical interventions were performed. Soft Palate Repair (SPR) and Hard Palate Repair (HPR) were performed with the DHPC procedure. The transfer to this technique was successfully performed in three steps: one team visit to Gothenburg by a surgeon from MSC and two visits by surgeons from Gothenburg to the MSC. Patients with SPR and HPR were operated on without major complications and there were no differences in results between Gothenburg surgeons and MSC surgeons. The interventions with SPR and HPR technique were proven to be easy to teach and learn and successfully performed without major complications. For cleft patients at MSC hospital it has meant earlier surgery, less re-operations and complications. This report shows a successful change of strategy for palatal repair with improved outcome regarding surgery. In future, speech and growth will be followed on a regular basis and will be compared with results from the Gothenburg Cleft Team.